Evaluation of the intragrain critical current density in a multidomain FeSe crystal by means of dc magnetic measurements. (25th September 2015) - Galluzzi, A; Polichetti, M; Buchkov, K; Nazarova, E; Mancusi, D; Pace, S
Abstract: The magnetic behavior of an iron-based FeSe crystal sample has been studied by means of dc magnetization measurements as a function of the temperature ( T ), the dc magnetic field ( H ) and the time ( t ). The M ( T ) curves show a discrepancy in the determination of the onset of the critical temperature T C with respect to what is observed in the superconducting M ( H ) measurements obtained by subtracting the ferromagnetic background from the curves measured at various temperatures. By using magnetic relaxation measurements M ( t ), the correct value of T C has been obtained. Moreover, the superconducting M ( H ) loops show the presence of a noisy signal up to an anomalous 'peak effect' only found for positive and negative increasing fields. These features have been analyzed by fitting the temperature dependence of the critical current density J c ( T ), extracted from the M ( H ) loops, with the help of the J c ( T ) dependencies governing an S–N–S junction network. This analysis has allowed us to interpret the behavior found in the M ( H ) loops and to obtain the value of the intrinsic critical current density J 0 which is not influenced by the presence of the junctions.